1999
DOI: 10.1021/om990055d
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Organolithium Reagents with Cyclorhenated and Cyclomanganated (η6-Arene)tricarbonylchromium Complexes:  Structural Characterization of a New Benzoylrhenate Intermediate and Selective Ortho-Acetylation of (η6-Arene)tricarbonylchromium Complexes

Abstract: The nucleophilic addition of PhLi to tetracarbonyl[3-methyl-2-{(η6-phenyl)tricarbonylchromium(0)}pyridine]rhenium(I) yields the air-stable (exo-benzoyl)(tricarbonyl)[3-methyl-2-{(η6-phenyl)tricarbonylchromium(0)-κ C 2‘}pyridine-κ N]rhenate(I) that has been isolated and characterized by X-ray diffraction analysis and other spectroscopic methods. A similar treatment applied to cyclomanganated (η6-arene)Cr(CO)3 analogues with a nucleophile such as MeLi provides a new route to the synthesis of ortho disubstituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Spectroscopic Detection of the [(Methoxy)(phenyl)methylidene]rhenium(I) Species 3. We recently underlined the synthetic versatility of the acylmanganate salts obtained from a reaction of RLi with a cyclomanganated (η 6 -arene)Cr(CO) 3 complex, as they could be valuable intermediates for the synthesis of ortho acyl-substituted (η 6 -arene)Cr(CO) 3 complexes . We described the X-ray diffraction structure of the rhenium analogue 2 that confirmed the stereoselectivity of the nucleophilic attack of PhLi at the Re(CO) 4 fragment of 1 (Scheme ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Spectroscopic Detection of the [(Methoxy)(phenyl)methylidene]rhenium(I) Species 3. We recently underlined the synthetic versatility of the acylmanganate salts obtained from a reaction of RLi with a cyclomanganated (η 6 -arene)Cr(CO) 3 complex, as they could be valuable intermediates for the synthesis of ortho acyl-substituted (η 6 -arene)Cr(CO) 3 complexes . We described the X-ray diffraction structure of the rhenium analogue 2 that confirmed the stereoselectivity of the nucleophilic attack of PhLi at the Re(CO) 4 fragment of 1 (Scheme ).…”
Section: Resultsmentioning
confidence: 91%
“…We showed that it was possible to control the absolute helicity of the final product by taking advantage of the metallocenic-like planar chirality existing in ortho -disubstituted (η 6 -arene)Cr(CO) 3 substrates bearing a chiral arene substituent. From a mechanistic standpoint, we demonstrated that the nucleophilic attack of a carbonyl ligand attached to Mn (or Re) by RLi was very sensitive to steric hindrance . Cyclomanganated (η 6 -arene)Cr(CO) 3 complexes would react selectively with PhLi to afford a unique benzoylmanganate complex resulting from the stereoselective addition of the lithiated agent at a Mn (or Re) attached carbonyl ligand located exo with respect to the sterically demanding group Cr(CO) 3 (Scheme , step A).…”
Section: Introductionmentioning
confidence: 99%
“…The insertion of carbene group into the M-C(N ∧ C) bonds in M(N ∧ C)(CO) 4 (M = Mn, Re) has been studied in detail by Djukic, Dötz, and Pfeffer and their co-workers. [23,24] It was found that treatment of Mn(CO) 4 (ppy) with PhLi followed by addition of MeOTf led to insertion of the carbene ligand C(Ph)(OMe) into the Mn-C(ppy) bond and the formation of a η 3 -benzyltricarbonyl Mn I complex 4 (Scheme 3).…”
Section: Transmetalation Of [Hg(ptpy) 2 ] With Ru Carbenementioning
confidence: 99%
“…For the synthesis of chromium manganese complexes we developed a strategy that combined the chromium-templated benzannulation of Fischer aryl carbenes with the cyclomanganation of an N-heterocyclic arene via intramolecular C−H activation . The starting material 5-bromobenzo[ h ]quinoline ( 1 ) was prepared according to the protocol reported for the synthesis of 5-bromoisoquinoline .…”
Section: Resultsmentioning
confidence: 99%
“…Upon warming, a thermo-induced metal migration provides the thermodynamically stable haptotropomer. With the aim of exploiting metal−metal interactions, heterobimetallic complexes have become a prominent field of organometallic research. , We became interested in whether the chromium migration can be controlled by another metal moiety coordinated to an extended π-platform. Recently, we reported on a chromium shift in binuclear (Cr, Mn) dibenzo[ c , e ]indene complexes .…”
Section: Introductionmentioning
confidence: 99%